Loss of function of the melanocortin 2 receptor accessory protein 2 is associated with mammalian obesity - Asai, Masato; Ramachandrappa, Shwetha; Joachim, Maria; Shen, Yuan; Zhang, Rong; Nuthalapati, Nikhil; Ramanathan, Visali; Strochlic, David E.; Ferket, Peter; Linhart, Kirsten-Berit; Ho, Caroline; Novoselova, Tatiana V.; et al. (Science, 2013)
Accessory to Obesity? - Melanocortin receptors are a family of cell membrane receptors that control diverse physiological functions. Mutations in the gene encoding melanocortin 4 receptor (MC4R) are a cause of familial early-onset obesity. Asai et al. (p. 275) studied the function of an accessory protein for MC4R signaling, MRAP2, and found that mice genetically deficient in MRAP2 develop severe obesity. Sequencing of MRAP2 in unrelated, severely obese humans revealed one individual with a clearly disruptive genetic variant, suggesting that MRAP2 mutations might also be a rare cause of human obesity. In a zebrafish model, Sebag et al. (p. 278) studied two paralogs of the MRAP2 accessory protein, one of which enhanced MC4R responsiveness to α-melanocyte-stimulating hormone, which regulates feeding and growth. - Melanocortin receptor accessory proteins (MRAPs) modulate signaling of melanocortin receptors in vitro. To investigate the physiological role of brain-expressed melanocortin 2 receptor accessory protein 2 (MRAP2), we characterized mice with whole-body and brain-specific targeted deletion of Mrap2, both of which develop severe obesity at a young age. Mrap2 interacts directly with melanocortin 4 receptor (Mc4r), a protein previously implicated in mammalian obesity, and it enhances Mc4r-mediated generation of the second messenger cyclic adenosine monophosphate, suggesting that alterations in Mc4r signaling may be one mechanism underlying the association between Mrap2 disruption and obesity. In a study of humans with severe, early-onset obesity, we found four rare, potentially pathogenic genetic variants in MRAP2, suggesting that the gene may also contribute to body weight regulation in humans. - Disruption of a protein required for effective signaling by a melanocortin receptor causes severe obesity in mice. - Disruption of a protein required for effective signaling by a melanocortin receptor causes severe obesity in mice.
Gesehen am 07.12.2020